Hemorragia subaracnóidea e síndrome de Terson: estudo prospectivo - Sung, Eun Song [UNIFESP] (2003)
PURPOSE: To analyze the incidence, clinical course, ophthalmic findings, and prognosis of the patients with intracranial bleeding and Terson's syndrome. METHODS: A prospective consecutive study of patients admitted to the emergency room with the diagnosis of acute subarachnoid hemorrhage. Neurological and funduscopic examinations were performed upon admission and at days 3, 7, 30 and 60 after the diagnosis. In all cases the clinical condition was graded according to the Hunt and Hess classification. RESULTS: Seventeen patients were enrolled in this study from July to October, 2000. Terson's syndrome was diagnosed in 5 of the patients (29.4%). Fifteen cases were associated with ruptured cerebral aneurysms, and the remaining two were caused by head trauma. There was no gender preponderance (9F:8M) and the median age was 48 years (range 22-80 years). Four of the five patients (80%) with Terson's syndrome died from intracranial complications, whereas 11 patients with intracranial bleeding and no ocular involvement survived. The leading cause of mortality was rebleeding. The ophthalmoscopic findings included intraretinal bleeding (3 cases), intraretinal and with subhyaloid hemorrhage (1 case) and intraretinal hemorrhage with cotton wool spots (1 case). CONCLUSIONS: In our study, the incidence of Terson's syndrome was 29.4% and it was associated with a high mortality rate (80%).